Silicon nitride plate and its manufacturing method
Patent Information
- Application Number
- JP2023041986
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-03-16
AI Technical Summary
【0029】 本発明によれば、複数種の厚さの窒化ケイ素板(薄板も含みうる)を、割れ、凹み及び変形を抑制しつつ、面積の大小に関わらず効率よく得ることができる。
Smart Images

Figure 0007637711000002 
Figure 0007637711000003 
Figure 0007637711000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride plate and a method for producing the same. [Background technology]
[0002] In recent years, the importance of thermal interface materials (TIMs) to fill the gap between heat-generating components and heat sinks has been recognized as a result of the trend toward higher power and smaller size of power devices. TIMs are required to have low thermal resistance, high strength, and thinness according to the application.
[0003] Currently, the most widely used TIM is made from a material in which highly thermally conductive ceramic particles (called filler), such as aluminum nitride, boron nitride, or alumina, are dispersed in resin, and this can be easily molded into a thin shape.
[0004] However, in TIMs made of the same material, heat is transmitted at the contact points between particles, so while it would be desirable to increase the particle packing density in order to reduce thermal resistance, there is a limit to how much the particles can be dispersed in resin, making it difficult to reduce thermal resistance beyond the current level.
[0005] Therefore, ceramic plates have been studied as a TIM with lower thermal resistance (Patent Document 1). The present inventors have focused on and studied sintered plates of silicon nitride (Si3N4) (hereinafter simply referred to as "silicon nitride plates"), which have high thermal conductivity as well as strength and fracture toughness.
[0006] Silicon nitride plates are generally manufactured by the following method (Patent Document 2). First, silicon nitride powder, sintering aids, binders, and other organic components are mixed to form a green sheet with a thickness of about 0.2 to 0.6 mm. Next, a separating agent is applied to the surface of the green sheet to prepare a laminate in which multiple green sheets are stacked. The laminate is fired to densify the green sheets to form silicon nitride plates, which are then separated into individual sheets.
[0007] However, it is difficult to directly manufacture a silicon nitride plate having a thickness smaller than the above by the above method for the following reasons (a) to (c).
[0008] (A) A problem occurs when some of the added sintering aid forms a liquid phase, volatilizes, and diffuses, causing the green sheets of the laminate to fuse slightly together. If the silicon nitride plate has a certain thickness, it is possible to peel off the fusion. However, if the silicon nitride plate is as thin as 0.1 mm, for example, the stress applied when peeling off the slightly fused silicon nitride plates will cause cracks. Even if cracks cannot be confirmed by visual inspection, fine cracks may occur, and a decrease in bending strength may be confirmed.
[0009] (a) In order to prevent the silicon nitride plates from fusing together, it is possible to increase the amount of release agent applied to the surface of the green sheet. However, the release agents used in the lamination process are generally boron nitride (BN) slurries or silicon nitride pastes that contain organic solvents. Therefore, if the amount of release agent applied is increased, the organic solvent will dissolve the binder components added to the thin green sheets, causing deformation of the green sheets.
[0010] (c) Furthermore, if an excessive amount of the separating agent is applied, it becomes lumpy and is likely to exist between the laminated green sheets, which can lead to defects such as dents and cracks.
[0011] Therefore, in the past, in order to obtain a silicon nitride plate with a small thickness, it was common to produce a silicon nitride plate with a thickness of, for example, about 0.2 mm using the above method, and then polish it to a thickness of, for example, about 0.1 mm, which resulted in low manufacturing efficiency. Therefore, it was difficult to obtain a silicon nitride plate with a large area using this method in terms of manufacturing efficiency. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2019-176060 A [Patent Document 2] JP 2011-178598 A Summary of the Invention [Problem to be solved by the invention]
[0013] Therefore, an object of the present invention is to efficiently obtain silicon nitride plates (which may include thin plates) of a variety of thicknesses, regardless of the size of their area, while suppressing cracks, dents, and deformation. [Means for solving the problem]
[0014] [1] A method for producing silicon nitride plates, comprising stacking green sheets of various thicknesses containing silicon nitride starting material via a separating agent, firing the sheets, and then separating the sheets after firing to obtain silicon nitride plates of various thicknesses.
[0015] [Effect] When green sheets of multiple thicknesses are stacked with a separating agent interposed therebetween and fired, even if the green sheets are slightly fused to each other, since one of the multiple thicknesses is relatively thicker than the others, the fusion can be removed and the sheets can be separated while suppressing cracking and deformation of the green sheets.
[0016] [2] The method for producing a silicon nitride board according to [1], wherein the starting material is silicon nitride powder or silicon powder. When the starting material is silicon nitride powder, the green sheet becomes a densified sintered body (silicon nitride plate) during firing, making nitridation unnecessary. When the starting material is silicon powder, the green sheet is nitrided during sintering and becomes a dense sintered body. If silicon powder with a low oxygen content is used, the amount of oxygen contained in the silicon nitride particles generated after nitriding can be reduced. Furthermore, the amount of oxygen in the liquid phase generated during sintering is reduced, and the nitrogen concentration is increased, which reduces the phase transition temperature to rod-shaped β-type silicon nitride particles and speeds up the grain growth rate of the β-type silicon nitride particles. As a result, the crystal grain size in the silicon nitride substrate after sintering becomes larger, and the thermal conductivity and surface roughness increase. In addition, the reduction in the amount of oxygen dissolved in the crystals also has the effect of increasing the thermal conductivity.
[0017] [3] The method for producing a silicon nitride board according to [1] or [2], wherein at least one of the green sheets having different thicknesses is a first green sheet having a thickness of 0.15 mm or less. It is possible to obtain a silicon nitride plate having a thickness of 0.15 mm or less, which can be used for applications requiring such a thickness.
[0018] [4] The method for producing a silicon nitride board according to any one of [1] to [3], wherein at least one of the green sheets having different thicknesses is a second green sheet having a thickness of 0.2 mm or more. It is possible to obtain a silicon nitride plate having a thickness of 0.2 mm or more, and the plate can be used for applications requiring such a thickness.
[0019] [5] The method for producing a silicon nitride substrate according to [3] or [4], wherein no releasing agent is applied to the surface of the first green sheet. Since the organic solvent contained in the separating agent does not dissolve the binder component added to the first green sheet, deformation of the sheet can be prevented.
[0020] [6] The method for producing a silicon nitride board according to any one of [3] to [5], wherein the first green sheets are not laminated continuously to each other. Since the first green sheets are not peeled away from each other, the cracks can be suppressed.
[0021] [7] Among the green sheets having a plurality of thicknesses, at least one is a first green sheet having a thickness of 0.15 mm or less, and at least one is a second green sheet having a thickness of 0.2 mm or more; A method for manufacturing a silicon nitride plate according to [1] or [2], comprising alternately laminating the second green sheet having a surface coated with a releasing agent and the first green sheet having a surface not coated with a releasing agent.
[0022] [8] A silicon nitride plate containing sintered silicon nitride particles, having a thickness of 0.12 mm or less, a three-point bending strength of 600 MPa or more (preferably 650 MPa or more), and a surface roughness Sa of 0.3 μm or more.
[0023] [Effect] The thickness is 0.12 mm or less, and the three-point bending strength is 600 MPa or more, which makes it suitable for use as a TIM, etc. In addition, the surface roughness Sa is 0.3 μm or more, which increases the adhesion to the heat dissipation grease or resin layer provided on the plate surface, and increases the thermal conductivity.
[0024] [9] The silicon nitride plate according to [8], wherein the silicon nitride particles are columnar β-type silicon nitride particles, and the surface roughness Sa is 2 μm or more.
[0025] The columnar β-type silicon nitride particles improve the thermal conductivity of the sintered body. In addition, the ends of the particles are exposed or protrude from the plate surface, which makes the surface roughness Sa 2 μm or more, further increasing the adhesion with the heat dissipation grease or resin layer, and increasing the thermal conductivity.
[0026]
[10] The silicon nitride plate according to [8] or [9], wherein at least one surface of the silicon nitride plate is a sintered surface. The sintered surface does not have a reduced surface roughness Sa.
[0027]
[11] The area of one surface of the silicon nitride plate is 2500 mm 2 The silicon nitride board according to any one of the above items [8] to
[10] . It is suitable for applications such as TIM where a large area is required.
[0028]
[12] The silicon nitride plate according to any one of [8] to
[11] , wherein a resin material is in contact with at least one surface of the silicon nitride plate. When another member is brought into close contact with that surface of the silicon nitride plate, the resin material makes it difficult for gaps to form, thereby increasing the thermal conductivity. Effect of the Invention
[0029] According to the present invention, silicon nitride plates (which may include thin plates) of a variety of thicknesses can be efficiently obtained regardless of the size of the area while suppressing cracks, dents, and deformation. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a schematic diagram illustrating a lamination step of green sheets in a method for producing a silicon nitride board according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a laser microscope photograph showing the surface microstructure of the silicon nitride substrate obtained in Example 1. [Diagram 3] FIG. 3 is a laser microscope photograph showing the surface microstructure of the silicon nitride substrate obtained in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The silicon nitride plate can be manufactured by a manufacturing method including a mixing step of mixing raw materials, a forming step of forming a green sheet by slurried raw materials, a lamination step of laminating the green sheets, a firing step of sintering the laminated green sheets to obtain a silicon nitride plate, and a separation step of separating the laminated silicon nitride plate. An example of each step will be described below.
[0032] In the mixing step, the starting material for the silicon nitride plate is, for example, silicon nitride powder or silicon powder. A sintering aid (rare earth oxide powder, magnesium compound powder, etc.) is added to the starting material, and the mixture is thoroughly mixed in a ball mill to adjust the particle size.
[0033] In the molding process, a binder, a plasticizer, and an organic solvent are added to the mixed powder to form a slurry, which is then vacuum degassed and the viscosity is adjusted. Green sheets of various thicknesses are molded from the slurry by a doctor blade method, an extrusion molding method, a casting method, or the like. Of the green sheets having a plurality of thicknesses, at least one is preferably a first green sheet having a thickness of 0.15 mm or less, and at least one is preferably a second green sheet having a thickness of 0.2 mm or more.
[0034] In the lamination step, green sheets of different thicknesses are laminated with a separating agent interposed therebetween to form a laminate. It is preferable that no separating agent is applied to the surface of the first green sheet, and that the first green sheets are not laminated continuously to each other. It is preferable that the second green sheets having a surface coated with a separating agent and the first green sheets having a surface not coated with a separating agent are laminated alternately.
[0035] In the firing process, if the starting material is silicon nitride powder, the green sheet stack is heated to densify the silicon nitride powder into a sintered plate. If the starting material is silicon powder, the green sheet stack is heated in a nitrogen atmosphere to nitride the silicon powder and densify it into a sintered plate (reaction sintering method). A first silicon nitride plate is obtained from the first green sheet, and a second silicon nitride plate is obtained from the second green sheet.
[0036] In the separation step, the silicon nitride plates obtained in a stacked state are peeled off one by one and separated.
[0037] By the above manufacturing method, it is possible to obtain a silicon nitride plate containing sintered silicon nitride particles, having a thickness of 0.12 mm or less, a surface roughness Sa of 0.3 μm or more, and a three-point bending strength of 600 MPa or more.
[0038] When the starting material is silicon powder, the silicon nitride particles are columnar β-type silicon nitride particles, and a silicon nitride plate having a surface roughness Sa of 2 μm or more can be obtained.
[0039] At least one surface of the silicon nitride plate, particularly the surface having the above-mentioned surface roughness Sa, is preferably a sintered surface.
[0040] In addition, if the area of one surface of the silicon nitride plate is, for example, 2500 mm 2 It is possible to obtain a silicon nitride plate having a large area as described above.
[0041] Also, a resin material may be in contact with at least one surface of the silicon nitride plate. The resin material is not particularly limited, but examples include thermosetting resin, reaction curing resin, photocuring resin, thermally conductive resin sheet, and resin with added highly thermally conductive filler (metal powder, ceramic powder, etc.). The form of the resin material is not particularly limited, but may be, for example, a resin layer.
[0042] Applications of the silicon nitride plate of the present invention are not particularly limited, but examples include TIM, circuit boards, heat sinks, insulating plates, and high-frequency windows. EXAMPLES
[0043] Next, Examples 1 to 6 shown in Table 1, which embody the present invention, will be described in comparison with Comparative Examples 1 to 3. Note that the materials, quantities, and conditions of each part in the examples are merely examples and can be appropriately changed without departing from the gist of the invention.
[0044] [Table 1]
[0045] First, a method for producing the silicon nitride plate of the first embodiment will be described. In the mixing process, α-type silicon nitride powder with a β-type silicon nitride content of 10% or less was used as the starting material for silicon nitride, and a sintering aid was added to make the composition shown in Table 1. An organic solvent (a mixed solvent of toluene and ethanol) and a dispersant were then added, and the mixture was mixed for 24 hours in a ball mill using silicon nitride grinding media. In the next molding step, a binder (polyvinyl butyral), a plasticizer (dioctyl adipate), and an organic solvent were added to the mixed powder to form a slurry. The slurry was vacuum degassed to adjust the ratio of the organic solvent in the slurry to 35 wt% or less, and the viscosity of the slurry was adjusted to 15,000 to 25,000 cps. From this slurry, a doctor blade was used to mold the first green sheet, which had a thickness of 0.12 mm after drying, and the second green sheet, which had a thickness of 0.45 mm after drying. Each of the obtained green sheets was cut into a size of 140 mm x 140 mm to prepare multiple sheets. In the next lamination process, a BN slurry containing an organic solvent was used as a separating agent, and as shown in Figure 1, second green sheets 2, on whose surfaces (both sides) the separating agent 3 had been sprayed and the organic solvent had been evaporated, and first green sheets 1, on whose surfaces (neither side) the separating agent had been sprayed, were alternately laminated from bottom to top, with the second green sheets 2 being placed at the bottom and top, to prepare a laminate consisting of 19 sheets in total, consisting of 9 first green sheets 1 and 10 second green sheets 2. In the next firing step, the laminate was debindered at 500°C in dry air and then fired at 1900°C for 4 hours to densify all the green sheets into sintered bodies (silicon nitride plates). A first silicon nitride plate was obtained from the first green sheet, and a second silicon nitride plate was obtained from the second green sheet. In the next separation step, the first silicon nitride plate and the second silicon nitride plate were peeled off one by one and separated.
[0046] Next, the manufacturing methods of silicon nitride plates of Examples 2 to 4 differ from Example 1 only in that in the molding process, the thicknesses of the first green sheet and the second green sheet were changed as shown in Table 1, and in that in the lamination process, the numbers of the first green sheet and the second green sheet and the amount of releasing agent applied to the second green sheet were changed as shown in Table 1; otherwise, they are the same as Example 1.
[0047] Next, the manufacturing methods of the silicon nitride plates of Examples 5 and 6 differ from that of Example 1 in the mixing step, molding step, lamination step, and firing step as described below, but are otherwise common to Example 1. In the mixing process, silicon powder with an oxygen content of 0.6 wt% or less was used as the starting material for silicon nitride, and an appropriate amount of silicon powder was placed in a resin pot, and the silicon powder, organic solvent, and dispersant were mixed with silicon nitride grinding media and the particle size was adjusted in a ball mill. The oxygen content of the silicon powder after particle size adjustment was 1.0 wt% or less. After that, a sintering aid was added to make the compounding composition shown in Table 1 (for silicon powder, the silicon nitride conversion is when silicon is completely nitrided to silicon nitride), and the mixture was mixed in a ball mill for 1 hour. In the molding process, the thicknesses of the first and second green sheets were changed as shown in Table 1. In the lamination process, the number of first green sheets and second green sheets and the amount of release agent applied to the second green sheets were changed as shown in Table 1. In the firing process, the laminate was debindered at 500°C in dry air, then heated to approximately 1000°C in a vacuum. The temperature was then increased from approximately 1000°C to approximately 1350°C at 1°C / min in a pressurized nitrogen atmosphere of 0.2 MPa to nitride all of the green sheets. The temperature was then increased from 1350°C to 1900°C in a pressurized nitrogen atmosphere of 0.9 MPa, and the green sheets were fired at 1900°C for 8 hours to form a densified sintered body (silicon nitride plate).
[0048] Next, the manufacturing method of the silicon nitride plate of Comparative Example 1 differs from that of Example 1 in that only the first green sheet formed in the molding process was used, and in the lamination process, 19 first green sheets, one side of which had been sprayed with a releasing agent and then the organic solvent was evaporated, were laminated to prepare a laminate, but the rest is the same as in Example 1.
[0049] Next, the manufacturing method of the silicon nitride board of Comparative Example 2 differs from Comparative Example 1 only in that the amount of the releasing agent applied to the first green sheet in the lamination step was changed as shown in Table 1.
[0050] Next, the manufacturing method of the silicon nitride board of Comparative Example 3 differs from Comparative Example 1 in that the mixing process is the same as that of Example 6, the thickness of the first green sheet is changed as shown in Table 1, the number of first green sheets and the amount of separating agent applied to the first green sheets in the lamination process are changed as shown in Table 1, and the firing process is the same as that of Example 6.
[0051] The outer circumference of the first silicon nitride plate and the second silicon nitride plate of Examples 1 to 6 and the first silicon nitride plate of Comparative Examples 1 to 3 produced as described above was cut by a laser to obtain a sample of 110 mm x 110 mm. The surface of the sample was the surface after sintering. The following observations and measurements were then performed on each sample.
[0052] (i) Cracks during the separation process The first green sheet samples were first visually inspected for cracks during the separation process, and those that did not show any cracks were further observed under a microscope. The results are shown in Table 1. None of the second green sheet samples had any cracks.
[0053] (ii) Thickness The thickness of the samples was measured using a micrometer with a double spherical head, and the results are shown in Table 1.
[0054] (iii) Three-point bending strength The substrates of each thickness were processed into test pieces with a total length of 40 mm and a width of 20 mm, and a three-point bending test was performed using a Shimadzu Corporation universal testing machine, model "AG-IS," at a crosshead speed of 0.5 mm / min, a support distance of 30 mm, and room temperature (23±2°C) to measure the three-point bending strength. The results are shown in Table 1.
[0055] (iv) Maximum depth of dent Among the samples of the first silicon nitride plate, there was one with a spot-like dent on the plate surface. It is considered that this dent was caused by the separating agent present between the sheets in the laminated state as a lump and being pressed by the separating agent. Therefore, the presence or absence of dents was confirmed by visual inspection, and the maximum depth of the largest dent among them was measured using a laser microscope VKX-150 manufactured by Keyence Corporation under the following conditions: objective lens magnification: ×20, image correction: automatic surface tilt correction, filter type: Gaussian, S-filter: 2 μm, F-operation: none, L-filter: 0.2 mm, end effect correction: yes. For those samples where dents could not be confirmed by visual inspection, measurement with a laser microscope was not performed.
[0056] (v) Surface roughness Sa The arithmetic mean height Sa, which is the surface roughness of a 500 μm × 500 μm area of the plate surface (sintered surface) of the first silicon nitride plate sample, was measured using a laser microscope VKX-150 manufactured by Keyence Corporation under the following conditions: objective lens magnification: ×20, image correction: automatic surface tilt correction, filter type: Gaussian, S-filter: 2 μm, F-operation: none, L-filter: 0.2 mm, end effect correction: yes. The results are shown in Table 1.
[0057] (vi) Observation of surface microstructure The plate surface (sintered surface) of the first silicon nitride plate sample was observed using a laser microscope VKX-150 manufactured by Keyence Corporation at an objective lens magnification of ×50. Fig. 2 shows the surface microstructure of Example 1, and Fig. 3 shows the surface microstructure of Example 6. In the silicon nitride substrate of Example 6 obtained by reactive sintering using silicon powder as the raw material, the grain growth of β-type columnar grains was more advanced than in the silicon nitride substrate obtained from the silicon nitride powder of Example 1 as the raw material.
[0058] [evaluation] The first silicon nitride plates of Examples 1 to 6 had a thickness of 0.12 mm or less, but were substantially free of cracks, dents and deformation, had a three-point bending strength of 600 MPa or more, and a surface roughness Sa of 0.3 μm or more. Specifically, the three-point bending strength was particularly high at 800 MPa or more, and the surface roughness Sa was 0.3 μm or more in Examples 1 to 4. The use of α-type silicon nitride powder as the starting material prevented excessive grain growth of β-type silicon nitride, so a high bending strength of 800 MPa or more could be obtained. In Examples 5 and 6, the three-point bending strength was 600 MPa or more, and the surface roughness Sa was particularly large at 2 μm or more. Since the grain growth of β-type silicon nitride was promoted by using silicon powder as the starting material, the bending strength was lower than that of Examples 1 to 4 due to stress concentration on the substrate surface. In contrast, the first silicon nitride plates of Comparative Examples 1 to 3 had cracks, dents and deformations, and the three-point bending strength was 530 MPa or less.
[0059] The first silicon nitride plate and the second silicon nitride plate in Examples 1 to 6 can also be made into a composite plate by sticking Kapton adhesive tape (Teraoka Seisakusho Co., Ltd., product number: 650S#12) as a resin layer on one side, for example.
[0060] The present invention is not limited to the above-described embodiment, and can be embodied by making appropriate modifications without departing from the gist of the invention. [Explanation of symbols]
[0061] 1. First Green Sheet 2. The Second Green Sheet 3. Separation agent
Claims
1. A method for obtaining silicon nitride plates of various thicknesses by laminating green sheets of various thicknesses containing silicon nitride starting material with a separating agent interposed therebetween and firing the laminated green sheets, and then separating the laminated green sheets after firing, comprising the steps of: Among the green sheets having a plurality of thicknesses, at least one is a first green sheet having a thickness of 0.15 mm or less, and at least one is a second green sheet having a thickness of 0.2 mm or more; A method for manufacturing a silicon nitride plate, comprising alternately laminating the second green sheet having a surface coated with a separating agent and the first green sheet having a surface not coated with a separating agent.
2. 2. The method for producing a silicon nitride plate according to claim 1, wherein the starting material is silicon nitride powder or silicon powder.
3. A silicon nitride plate containing sintered silicon nitride particles, having a thickness of 0.10 mm or less, a three-point bending strength of 600 MPa or more, and a surface roughness Sa of 0.3 μm or more, At least one surface of the silicon nitride plate is a sintered surface.
4. The area of one surface of the silicon nitride plate is 2500 mm 2 4. The silicon nitride plate according to claim 3.
5. 5. The silicon nitride plate according to claim 3, wherein at least one surface of the silicon nitride plate is in contact with a resin material.
Citation Information
Patent Citations
Ceramic substrate and its polishing
JP1999335158A
Method for manufacturing silicon nitride substrate and silicon nitride substrate
JP2011178598A
Silicon nitride sintered substrate, electronic apparatus, and method for manufacturing the silicon nitride sintered substrate
JP2019052072A
Electrically insulative heat conductive sheet and method of manufacturing the same
JP2019176060A
Sintered silicon nitride substrate and process for producing same
WO2013146789A1